Axonal transport of Frizzled5 by Alcadein α-containing vesicles is associated with kinesin-1 - Shiraki, Yuzuha; Mitsuma, Monet; Takada, Ritsuko; Hata, Saori; Kitamura, Akira; Takada, Shinji; Kinjo, Masataka; Taru, Hidenori; Müller, Ulrike C.; Yamamoto, Tohru; Sobu, Yuriko; Suzuki, Toshiharu (Molecular biology of the cell, 2023)
Alcadein α/Alcα is a cargo receptor that associates vesicles with kinesin-1. - - Alcα vesicles include characteristic proteins in adult brain neurons. - - Lack of Alcα impairs signal transduction at nerve terminals.